A audiência de custódia e sua incapacidade de contenção do poder punitivo - Monteiro Neto, Figueiredo (2018)
Brazilian criminal policy has been oriented by criminal policies increasingly concerned with vigilance, control and neutralization of individuals considered to be dangerous, especially after the country’s redemocratization, in the late 80's of the twentieth century, having as paradigmatic framework and edition of the Law of Hideous Crimes - Law 8.072/90. This process has led us to what has become known as the super-incarceration society, in which Brazil occupies the position of the third country that most arrests people in the world, with now more than 700,000 prisoners in the prison system, with 40% of them being provisional prisoners awaiting a trial. It is about this process that custody hearing is intended to interfere, by placing face to face the prisoner and the judge, in order for the magistrate to analyze the prisoner's custody situation within a maximum of 24 hours from the arrest. Interestingly, however, the Resolution 213/15, from the National Council of Justice, which made custody hearing mandatory for all Courts in the country after May 1st , 2016, prevents it from being discussed at this hearing the fact by which a person was arrested, being characterized, therefore, as another instrument of subjection of the individual, depriving them of one of the rights that stand out most in the process of citizenship, which is the right of speech and decision-making influence in public life. It is not for another reason that the custody hearing was not only unable to reduce the number of incarceration in the city of Umuarama, where the research was conducted, but saw it grow in the first year after its implementation.